Coupling non-thermal plasma with Ni catalysts supported on BETA zeolite for catalytic CO2 methanation. Issue 15 (17th July 2019) - Chen, Huanhao; Mu, Yibing; Shao, Yan; Chansai, Sarayute; Xu, Shaojun; Stere, Cristina E.; Xiang, Huan; Zhang, Rongxin; Jiao, Yilai; Hardacre, Christopher; Fan, Xiaolei
Abstract : Non-thermal plasma activation promotes CO2 conversion over Ni catalysts supported on BETA zeolite via multiple reaction mechanisms. Abstract : Catalytic carbon dioxide (CO2 ) methanation is a promising and effective process for CO2 utilisation and the production of CH4 as an alternative to using natural gas. Non-thermal plasma (NTP) activation has been proven to be highly effective in overcoming the thermodynamic limitation of reactions under mild conditions and intensifying the CO2 hydrogenation process greatly. Herein, we present an example of NTP-assisted catalytic CO2 methanation over Ni catalysts (15 wt%) supported on BETA zeolite employing lanthana (La) as the promoter. It was found that a NTP-assisted system presents remarkable catalytic performance in catalytic CO2 methanation without an external heat source. Significantly, the use of Na-form BETA zeolite and the addition of La ( i.e. 15Ni–20La/Na-BETA catalyst) resulted in an improvement in CO2 conversions, surpassing the 15Ni/H-BETA catalyst, i.e. a seven-fold increase in the turnover frequency, TOF (1.45 s −1 vs. 0.21 s −1 ), and selectivity towards CH4 (up to ca. 97%). In addition, the developed catalyst also exhibited excellent stability under NTP conditions, i.e. a stable performance over a 15 h longevity test (with a TOF of 1.44 ± 0.01 s −1 ). Comparative in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) characterisation of the developed catalysts revealed that the introduction of La2 O3 to the Ni catalyst provides more surface hydroxyl groups, and hence enhances CO2 methanation. Additionally, by analysing the surface species over 15Ni–20La/Na-BETA comparatively under thermal and NTP conditions (by in situ DRIFTS analysis), it is proposed that both the Langmuir–Hinshelwood and Eley–Rideal mechanisms co-exist in the NTP system due to the presence of dissociated H species in the gas phase. Conversely, for the thermal system, the reaction has to go through reactions between the surface-dissociated H and carbonate-like adsorbed CO2 via the Langmuir–Hinshelwood mechanism. The current mechanistic understanding of the NTP-activated system paves the way for the exploration of the reaction mechanisms/pathways of NTP-assisted catalytic CO2 methanation.